Free and glycosylated green leaf volatiles, lipoxygenase and alcohol dehydrogenase in defoliated Nebbiolo grapes during postharvest dehydration. (28th September 2021) - Piombino, P.; Genovese, A.; Rustioni, L.; Moio, L.; Failla, O.; Bellincontro, A.; Mencarelli, F.
Abstract: Background and Aims: Nebbiolo grapes are used to produce Sfursat wine, following partial dehydration. This research aimed to clarify the influence of fruit exposure to light and postharvest water loss on the concentration of green leaf volatiles (GLVs) and lipoxygenase (LOX) and alcohol dehydrogenase (ADH) activity of grapes. Methods and Results: Nebbiolo grapes from Control vines (no defoliation) (ND) and from vines defoliated at fruitset (DFS) or defoliated post‐veraison (DPV) were harvested at about 23°Brix and dehydrated at 10 and 20°C, 60% RH and air flow of 1.5 m/s. Berries were sampled at 10 and 20% mass loss (ML). Significant differences in crop yield, bunch mass and berry mass were observed. As expected, the higher the dehydration temperature, the faster the dehydration process: 20% ML at 20°C occurred between 18 and 25 days, the shortest time corresponding to ND and the longest to DFS; at 10°C, the dehydration lasted between 27 and 32 days. At 10°C, the ADH activity was almost double that at 20°C, and in DFS was much higher than in other samples. At harvest, LOX did not show any difference among the samples, while at 10°C and 10% ML, the enzyme activity increased significantly and then declined at 20% ML, especially in defoliated samples. At harvest, the total free GLVs associated with the metabolism of lipid oxidation were 9434, 7212 and 11 656 μg/kg dry weight (DW) in ND, DFS and DPV samples, respectively; the total bound GLVs lipid‐derived were 7599, 18 486 and 15 409 μg/kg DW in ND, DFS and DPV samples, respectively. During dehydration at 10°C, the ML induced ADH + LOX activity, especially in defoliated samples, but the bound GLVs, produced by defoliation, greatly decreased. Conclusions: Defoliation affected the response of Nebbiolo grapes to dehydration temperature: postharvest cold stress (10°C) and ML induced glycosylation of GLVs, alcohol formation (via ADH) and membrane oxidation (via LOX); a further stress effect was observed with leaf removal, regardless of the time of application. Significance of the Study: The timing of defoliation and postharvest dehydration temperature are significant factors to mitigate the postharvest stress response of Nebbiolo grapes.